Subgingival utilization of a 1% chlorhexidine collagen gel for the treatment of periodontal pockets. A clinical and microbiological study. - Vinholis, A. H.; Figueiredo, L. C.; Marcantonio Júnior, Elcio [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP]; Salvador, S. L.; Goissis, G. (My University, 2001)
This study evaluates the effect of subgingival irrigation with a 1% chlorhexidine collagen gel in periodontal pockets as an adjunct procedure to scaling and root planing (SRP). Thirty-seven sites with probing depth (PD) of 5-7 mm and BANA positive in 6 patients with chronic periodontal disease were selected. Sites were assigned to different treatment groups consisting of SRP only (group 1), SRP + irrigation with collagen gel (group 2), or SRP + irrigation with collagen gel containing 1% chlorhexidine (group 3). Subgingival irrigation was performed after initial SRP and at 7, 14 and 21 days. Clinical measurements including PD, plaque index (PI), gingival index (GI), gingival recession (GI), bleeding on probing (BOP) and clinical attachment level (CAL) were performed at the selected sites at baseline, 60 and 90 days and the BANA test was performed on plaque samples from the same sites at baseline and 90 days. There was an improvement in clinical parameters in all groups with a significantly greater decrease in GI and bleeding in the chlorhexidine group. There was a greater reduction of BANA positive sites in groups 2 and 3. The authors concluded that 1% chlorhexidine collagen gel is a promising adjunct to SRP in the treatment of adult periodontitis.
Keywords: chlorhexidine; collagen; n benzoylarginine 2 naphthylamide; topical antiinfective agent; adult; analysis of variance; chi square distribution; clinical trial; controlled clinical trial; controlled study; female; gel; gingiva disease; human; lavage; male; middle aged; nonparametric test; periodontics; periodontitis; preventive dentistry; tooth plaque; treatment outcome; Adult; Analysis of Variance; Anti-Infective Agents, Local; Benzoylarginine-2-Naphthylamide; Chi-Square Distribution; Chlorhexidine; Collagen; Dental Plaque Index; Dental Scaling; Female; Gels; Gingival Recession; Humans; Irrigation; Male; Middle Aged; Periodontal Index; Periodontal Pocket; Statistics, Nonparametric; Treatment Outcome